2017
DOI: 10.1111/srt.12371
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of non‐invasive body tightening with high‐intensity focused ultrasound (HIFU)

Abstract: HIFU safely and effectively improves skin elasticity and clinical contouring of the face and body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 13 publications
1
46
0
Order By: Relevance
“…It is estimated that the device heats tissue to the critical temperature of 65‐75°c at which collagen denaturation occurs and stimulates the tissue repair cascade. Collagen contraction and remodeling occurred around microcoagulation zones can cause skin tightening on treated area . Wondergem et al reported the effect of local heat treatment on the motor function of the rat sciatic nerve at the temperatures from 42‐45°c resulting in motor function evaluated using the toe‐spreading test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that the device heats tissue to the critical temperature of 65‐75°c at which collagen denaturation occurs and stimulates the tissue repair cascade. Collagen contraction and remodeling occurred around microcoagulation zones can cause skin tightening on treated area . Wondergem et al reported the effect of local heat treatment on the motor function of the rat sciatic nerve at the temperatures from 42‐45°c resulting in motor function evaluated using the toe‐spreading test.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, FDA approved the use of HIFU for eyebrow lifting, followed by a neck and submental lifting. However, off‐label applications for facial rejuvenation, skin whitening, hyperhidrosis, acne, and lipolysis have been employed . The tightening effect of HIFU is the result of transcutaneous coagulative heating to specific area of the dermis and subcutaneous tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focal depth and energy output on these devices can be adjusted based on the thickness of the patient's facial and body skin, which ultimately determines the treatment outcome . Each procedure lasts for approximately 30–90 min, depending on the treatment location on the body.…”
Section: Ultrasound Skin Tightening and Body Contouringmentioning
confidence: 99%
“…The demand for noninvasive esthetic procedures for skin tightening increases. Technologies such as Radiofrequency (RF), High‐intensity Focused Ultrasound (HIFU), Laser, Infrared IR), and pressure energy devices are used to improve the esthetic appearance and self‐confidence of patients.…”
Section: Introductionmentioning
confidence: 99%